Analisis Kesulitan Belajar Siswa pada Materi Penjumlahan Kelas II di SDN Keboncau IV - Damayanti, Desyka; Rini, Candra Puspita; Yenni, Yenni (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to describe and explain what are the types of student learning difficulties in grades 2 summation material at SDN Keboncau IV, this research uses a qualitative approach and a qualitative description research method. Subjects in this study were grade 2 students, totatling 5 students. Data collection techniques using observation, interviews and tests in the form of essays totaling 5 questions. The addition material test is used to strengthen students’ answers regarding their understanding of the addition material. It can be concluded that the dominant difficulties occur in grade 2 at SDN Keboncau IV, namely difficulties in arithmetic, difficulties in connecting concepts with existing reality, and difficulties in solving addition problems in the form of stories.